Chitosan coating and packaging to maintain the physical quality of beet tubers - Garusti, Garusti; Indradewa, Didik; Handayani, Valentina Dwi Suci; Putra, Eka Tarwaca Susila; Nurwita, Ardian (AGROINTEK, 2025)
Beet tubers are perishable horticultural commodities, cannot be stored for long, and are commonly consumed in fresh conditions. Postharvest handling of beet tubers needs to be carried out to maintain their freshness Chitosan and other packaging used in postharvest handling of fresh beet tubers have not yet been reported. This study aims to determine the effect of chitosan coating and types of packaging on beet tubers on the physical quality of beet tubers. The study was a randomly designed group with two factors; the first factor was chitosan concentration, and the second factor was the kinds of packaging. Chitosan concentration consists of 5 levels, namely 0, 0.5%, 1%, 1.5%, and 2%, and the type of packaging includes no packaging (Without), plastic packaging with holes (Perforated), ordinary plastic packaging (Ordinary) and plastic vacuumed (Vacuum). The beet tubers were soaked in chitosan solution of 0, 0.5%, 1%, 1.5%, and 2% for 1 minute, air-dried, then were packaged with no packaging, plastic packaging with holes, ordinary plastic packaging, and plastic vacuumed. .  The physical quality parameters observed were moisture content, weight loss respiration rate,electrolyte leakage, total dissolved solid (TDS), ascorbic acid, betacyanin, betaxanthins,  tuber firmness, damage percentage, and visual quality rating (VQR). Data were analyzed using Anova variant analysis and then continued with Tuckey tests with a 95% confidence level using R studio software. The results showed that chitosan coating did not affect the physical quality of beet tubers, while packaging affected the quality of beet tubers. The most suitable packaging to maintain the physical quality of beet tubers is plastic packaging with holes (perforated).